Interfacing TiO2(B) nanofibers with Li4Ti5O12 towards highly reversible and durable TiO2‐based anode for Li − ion batteries - Ho, Ching-Kit (2020)
Nanostructured TiO2(B) suffers from severe initial irreversible capacity loss (ICL) (≥15 %), hindering its commercialization. While the incorporation of stable Li4Ti5O12 with negligible ICL into TiO2(B) should address the issue, the synthesis of TiO2(B)/Li4Ti5O12 composite remains unexploited because the conventional synthesis temperature required for the Li4Ti5O12 formation induces growth of anatase TiO2. Here, we achieve the first synthesis of TiO2(B)/Li4Ti5O12 nanocomposite by interfacing high‐energy (020) planes of TiO2(B) nanofibers and Li4Ti5O12 with a small lattice mismatch. As a new class of Li‐ion battery anode, the TiO2(B)/Li4Ti5O12 nanocomposite features a significantly mitigated initial ICL (7 % at 35 mA g−1), stable cycling (93 % capacity retention after 1000 cycles at 1750 mA g−1), and enhanced rate performance (122 mAh g−1 at 2630 mA g−1). This can be mainly attributed to the synergistic effect of the composition and structure resulting in reduced and stabilized SEI formation. Demonstrating the first success of synthesizing a TiO2(B)/Li4Ti5O12 composite, this work provides insights to the effective integration of compounds requiring high synthesis temperature with metastable phases.